The Effects of Dexamethasone on Periodontitis and the Influence of this Disease in Development and Survival of Mice Ovarian Follicles - Alexsandro Farias de Sá; Débora Ferreira Gomes; Ilan Matheus Leandro Araújo; Rebecca Beatriz Alves Lima; Antonia Letícia Costa Vasconcelos; Jonas Costa Monteiro; Guilherme Melo Gomes; Ernando Igo Teixeira de Assis; Jordânia Marques de Oliveira Freire; Anderson Weiny Barbalho Silva; Iracema Matos de Melo; José Roberto Viana Silva (Archives of Current Research International, 2025)
Aims: To investigate the effects of periodontitis, alone or in combination with dexamethasone treatment, on the growth, viability, and cyclicity of ovarian follicles in mice. Study Design: The animals were divided into four different groups, kept in polyethylene boxes, with eight animals per box. Place and Duration of Study: It was performed in the Federal University of Ceara, between January 2021 and December 2021. Methodology: Swiss mice (N=32) were divided into four groups: naive, treatment with dexamethasone, with periodontitis and with periodontitis and treatment with dexamethasone. To induce periodontal disease, 4.0 cotton threads was placed around the lower first molars, over two months, from January to February 2021. Dexamethasone (0.5 mg/kg) was administered intramuscularly, every three days, over two months. After this period, from March to April 2021, the mandibles were decalcified with EDTA and the analysis was carried out in the subsequent months. At the end of treatment, alveolar bone and periodontal attachment losses were evaluated. Furthermore, ovarian follicles were classified as normal or degenerated, as well as primordial, primary, secondary or tertiary follicles. Results: The ligature on the lower first molar significantly increased (P < 0.0001) the alveolar bone loss in mice that received only saline compared to those in which periodontitis was not induced. Treatment with dexamethasone did not promote significant (P > 0.05) changes in animals in which periodontitis was not induced. Animals with induced periodontitis and those with periodontitis and treated with dexamethasone showed a significant increase in estrous cycle irregularity. Periodontitis, or periodontitis associated with dexamethasone treatment significantly reduced the percentages of normal secondary and tertiary follicles. Conclusion: Periodontitis significantly increases the degeneration of secondary and tertiary ovarian follicles, while dexamethasone does not influence follicular morphology but contributes to estrous cycle dysregulation.